An exploration in the similarities between two ancestral houses in Obando,Bulacan with other houses of the same era - Marifosque, Rachael Allera
This thesis aims to identify and describe the similarities of the two ancestral houses located in Obando, Bulacan with other bahay-na-bato of their same era. Specifically, it sought to answer the following questions: 1. What similarities do these houses have in terms of architectural style, fixtures, interiors and other furniture pieces and decorative arts? 2. What motifs could indicate that they belong to the same era? 3. What are the relationships between the character and lifestyle of the owners and the style or construction of their houses? 4. Do their lifestyles affect the interior and general construction of the house? This thesis arrived at the conclusion that these two houses were typical of others of the same period as evidenced by their similar construction and floor plans, the ornaments and interior motifs used.